Nonsteroidal Anti-Inflammatory Drug Hypersensitivity in Preschool Children - Kidon Mona (Allergy, Asthma & Clinical Immunology, 2007)
Although extensively studied in adults, nonsteroidal anti-inflammatory drug (NSAID) hypersensitivity in children, especially in young children, remains poorly defined. Pediatricians, prescribing antipyretics for children, rarely encounter significant problems, but the few epidemiologic studies performed show conflicting results. Although it is clear that some patients with acetylsalicylic acid (ASA)-sensitive asthma have their clinical onset of disease in childhood and bronchoconstriction after ASA challenge is seen in 0 to 22% of asthmatic children so challenged, ibuprofen at antipyretic doses may cause acute respiratory problems only in a very small number of mild to moderate asthmatics. The recently elucidated mechanism of action of acetaminophen may explain some occurrences of adverse reactions in patients with cross-reactive NSAID hypersensitivity on the basis of its inhibitory activity on the newly described enzyme, cyclooxygenase (COX)-3. This nonspecific sensitivity to inhibition of COX is most likely genetically determined and shows a remarkable association with atopic disease even in the very young age group and possibly an increased predilection in specific ethnic groups. This review summarizes state-of-the-art published data on NSAID hypersensitivity in preschool children.